DASAR ALKITABIAH MENERIMA IBADAH ONLINE MENURUT FILIPI 3:3 - Prabowo, Wisnu (P3M STT Kristus Alfa Omega, 2021)
In the life of a Christian, the Holy Spirit has a very important role. In every detail of their lives, Christians believe that the Holy Spirit directs and guides them. Worship of God by Christians includes those directed and guided by the Holy Spirit. But there are still Christians who prioritize and think about external or worldly things as the main requirement to be able to worship God. Nowadays, worship is mostly done with online worship procedures. However, online worship gets a less religious impression when compared to worship that is carried out in person in a church building. The Apostle Paul emphasized in Philippians 3:3 that every Christian can worship only because of God's grace and also because of the guidance of the Holy Spirit. Christians should no longer depend on external things to come to worship God. This study is a qualitative research using inductive exegesis research methods and bibliography. This study examines the phrase â€œwho worship God in the Spiritâ€ found in Philippians 3:3. The results of the study obtained are: First, Christians experience very strong pressure and temptation to think about external things in worshiping God. Second, Christians must prioritize a spiritual life led by the Holy Spirit in their worship of God, because worship is a gift from God. Both of these results prove that worship carried out using online procedures has the same religious value as worship carried out in church buildings.